TAFSIR KONTEKSTUAL ATAS MODERASI DALAM AL-QUR’AN: SEBUAH KONSEP RELASI KEMANUSIAAN - Mahbub Ghozali; Derry Ahmad Rizal (Jurnal Studi Agama dan Masyarakat, 2021)
This study focused on the meaning of the word moderate in the Qur'an contextually with reference to the QS. [2]: 143 and QS. [5]: 66. The idea of  concept on religious moderation  was still related to the meaning and urgency of moderate attitude by linking this attitude to the behavior of certain religious people. There were three problems in this study, (1) what was the form of the meaning of wasth and muqtashid? (2) what were the factors behind the meaning? (3) how the contextual meaning was generated. To respond the research problem, this study used a qualitative method using content analysis. This study revealed that the mention of moderate party in the Qur'an was not limited to Muslims, but also refers to other people. This was based on the similarity of meaning between the word wasth which was used to refer to Islam and muqtasid which was used to refer to Jews and Christians. Moderate was thus not identical to religion, but it was oriented to the attitude of humanity owned by everyone regardless of religion. Moderation thus did not always indicate the relationship between religion, but the relationship between human being.